Proportion of Grassland at Landscape Scale Drives Natural Pest Control Services in Agricultural Landscapes - Perrot, Thomas; Rusch, Adrien; Coux, Camille; Gaba, Sabrina; Bretagnolle, Vincent (Frontiers in Ecology and Evolution, 2021)
Managing regulating ecosystem services delivered by biodiversity in farmland is a way to maintain crop yields while reducing the use of agrochemicals. Because semi-natural habitats provide shelter and food for pest enemies, a higher proportion of semi-natural habitats in the landscape or their proximity to crops may enhance pest control in arable fields. However, the ways in which the spatial arrangement of these habitats affects the delivery of this beneficial ecosystem service to crops remains poorly known. Here, we investigated the relative effects of the amount of grassland in the landscape versus the distance to the nearest grassland on the predation rates of weed seeds and aphids into 52 cereal fields. We found that both seed and aphid predation levels increased with the proportion of grassland in a 500 m radius buffer while the distance to the nearest grassland displayed no effect. We show that increasing from 0 to 50% the proportion of grasslands in a 500m radius respectively increased seed and aphid predation by 38% and 20%. In addition to the strong effect of the proportion of grassland, we found that seed predation increased with the proportion of forest fragments while aphid predation increased with the proportion of organic farming in the landscape. Overall, our results reveal that natural pest control in cereal crops is not related to the distance to the nearest grassland, suggesting that natural enemies are not limited by their dispersal ability. Our study indicates that maintaining key semi-natural habitats, such as grasslands, is needed to ensure natural pest control and support food production in agricultural landscapes.